INTERNATIONAL LEGAL FRAMEWORK FOR COMBATING CLIMATE CHANGE - Ismailova , Malika Zamirovna (Educational Research in Universal Sciences, 2023)
This article introduces an overview of the international legal framework for combating climate change. It examines the key international documents regulating the activities of States in the fight against climate change. It is discussed that the main changes in the field of climate after the adoption of key international documents. Particular attention in this article is paid to the role of the United Nations and other climate organizations in the formation and development of an international legal framework to combat climate change.